Segmenting the Baby Boomer generation: An example of Croatian consumers - Ivana Pavlić; Katija Vojvodić; Barbara Puh (Ekonomski Vjesnik, 2018)
In today’s world, demographic ageing has become a global phenomenon that emphasizes the need for researching older consumers’ retail purchasing patterns and behaviour. Previous research failed to address this demographic segment in the context of the retail environment in Croatia. With this in mind, the present paper focuses on Croatian Baby Boomers in order to examine their level of satisfaction and loyalty to retail stores. The main purpose of this paper is to broaden current knowledge of Baby Boomers’ retail store attitudes and retail behaviour in order to identify distinct categories of this ageing segment. Therefore, empirical research was conducted from 1 June to 1 October 2016 using a purposive sample of 169 Baby Boomers. In order to achieve the main aim of this paper, cluster analysis, ANOVA and the t-test were used. The results reveal that Croatian Baby Boomers can be segmented into three main clusters, each with their specific characteristics. This research has given rise to many questions in need of further examination of this growing segment in order to better understand their behaviour.